Late payment practices in the malaysian construction industry - Mohd Badroldin, Mohd Khairul Anas (Faculty Of Civil Engineering, UTM, 2016)
Factors that influence contractors „cash flow are the frequency of payment, delay , profit margin, retention fund, payment term to the supplier and subcontractor, advanced payment and others. L ate payment from the client has become a habit in the construction industry and this practice had cause d many implications such as bankruptcy, the higher contract sum due to higher risk, uncomfortable relationship between the payer and payee, disturbance of supply chain and others. The aim of this paper is to examine the late payment practices in the Malaysi an construction industry. Thirty seven (37) sets of questionnaire had been collected among the Grade G7 contractors and subcontractors in the state of Selangor based on convenience sampling . The collected data were analysed by using frequency distribution and relative important index (RII). The Data then was tabulated and illustrated in the form of charts. The results of the study show that the late payment is one of the most critical proble ms in the Malaysian construction industry. The majority of the contractor experienced late payment quite frequently and even beyon d the stipulated contract term. The top three impacts of the late payment problems are the negative chain effe ct on other part ies, delay in project completion and lead to bankruptcy or liquidation.